Heart failure with preserved ejection fraction (HFpEF) pathophysiology study (IDENTIFY-HF): rise in arterial stiffness associates with HFpEF with increase in comorbidities. (14th October 2021) - Ali, D; Tran, P; Weight, N; Ennis, S; Weickert, M; Miller, M; Cappuccio, F; Banerjee, P
Abstract: Background: There has been a shift in paradigm proposing that comorbidities play a significant role towards the pathophysiology of the heart failure with preserved ejection fraction (HFpEF) syndrome. Further, HFpEF patients have abnormal macrovascular function, potentially contributing significantly in altered ventricular-vascular coupling in these patients. However, our full understanding of the role of comorbidities, arterial stiffness and it relationship with HFpEF remains incomplete. Purpose: The IDENTIFY-HF study aims to shed light on the HFpEF pathophysiology and investigates whether gradually increase in arterial stiffness (in addition to ageing) due to increasing common comorbidities, such as hypertension and diabetes, is associated with HFpEF. Methods: Arterial compliance was assessed in five groups (Groups A to E) matched for age, (≥70 years), sex and renal function: Group A; normal healthy volunteers without major comorbidities (control). Group B; patients with hypertension only. Group C; patients with hypertension and diabetes mellitus only. Group D; patients with HFpEF. Group E; patients with heart failure and reduced ejection fraction (HFrEF); the parallel group. Arterial compliance was assessed using pulse wave velocity (PWV), as the primary outcome measure and was compared between Group A to D. A separate comparison was made between Groups D and E. To avoid confounding factors, participants were asked to omit their morning blood pressure medication and abstain from caffeine for 12 hours prior to the study. Results: From the 95 volunteers recruited, PWV was obtained in 94 subjects. The mean PWV in group A, B, C, D and E was 10.2-, 12.2-, 13.0-, 13.7- and 10.0 m/s respectively. After adjusting for covariance (age, sex, BMI and renal function), the mean difference between Group A (healthy volunteers) and D (HFpEF) was 2.14 m/s (p=0.023). Whilst the mean difference between the HFpEF and HFrEF group D and E respectively was 2.68 m/s (p=0.003). Conclusion: Rise in comorbidities increases arterial stiffness, as measured by pulse wave velocity, which in turn significantly associates with HFpEF (p=0.023). It is therefore possible that the HFpEF syndrome may not be due to a primary cardiac pathology but rather an end-result of non-cardiac comorbidities affecting vascular resistance with perhaps some secondary cardiac involvement. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): 1)West Midlands Clinical Research Network, National Institute of Health Research, UK2)Research, Development & Innovation department of the University Hospitals Coventry & Warwickshire NHS Trust (RDI, UHCW), UK.